Towards a Stable Nash Equilibrium of the Game of Global Covid Lockdown - R. Pazhanisamy; E. Selvarajan (Department of Humanities and Social Sciences (HSS), Jain University Global Campus, 2020)
Various attempts have been made to reveal the impact of corona virus on the global economy through interdisciplinary approaches. The ultimate logic behind the strategies adopted by leaders of various economies regarding the first level policy response of lockdown and the and the end level solution through low cost responsive vaccine with zero negative externalities has raised a self-sustainable crux which raise the question of why the world is not yet reached “Global Nash Equilibrium” in which all countries may reach a Covid fear free economy. In this context the present is attempt to fill this gap by developing a game theory based model. Keeping the present market structure for the vaccine and it is also predicted that demand curve for the vaccine even if it is in competitive price level become flat.
Additional information: Disclaimer: The views appeared in the works are of the authors only. In no way it reflects the institutions in which they belong to.
Keywords: C73; D03; D43; C72; D81; F00; 330; Non cooperative Games; Nash Equilibrium; Global Equilibrium; lockdown Economics; Demand Curve for Covid Vaccine; supply curve of Covid vaccine